?MONITORING THE QUALITY OF SUNFLOWER SEED BEFORE AND DURING STORAGE - SIDDIQUI, NAJEEB UDDIN; AHMAD, SYED IRFAN; HAIDER, IFfIKHAR (Biological Sciences - PJSIR, 1996)
Storage life of sunflower seed can be increased by monitoring the quality of seed before and during the storage period. Cold test, accelerated and modified accelerated aging test, in which several germination tests were made over time were evaluated. Modified accelerated aging test was found to be a more reliable method of seed quality evaluation. Seed lots having P50 viability period (period when germination drops to 50%) of 3.5 and above could be stored safely upto one year in conducive environmental conditions.